Opportunities or challenges? The interplay between artificial intelligence and corporate social responsibility communication - Xiangzhou Hua; Nurul Ain Mohd Hasan; Feroz De Costa; Weihua Qiao (Business Systems Research (BSR), 2024)
Background The rapid development of Artificial Intelligence (AI) offers both opportunities and challenges for its application in Corporate Social Responsibility (CSR) communication. While AI can enhance CSR initiatives, its impact on consumer relations and brand perception remains inconsistent. Objectives This study aims to explore the academic landscape of AI's role in CSR communication, focusing on publication trends, key authors, research topics, and future directions. Methods/Approach A bibliometric analysis was conducted on 1,094 articles related to AI and CSR communication, retrieved from the Web of Science database from 2000 to February 2024. Using CiteSpace software, the study mapped research trends by analysing disciplines, countries, institutions, authors, references, and keywords. Results The United States and China lead in publication output, with key research themes including social media impact, management strategies, and consumer trust. Emerging trends point to the importance of privacy, service quality, and perceived value in AI-driven CSR initiatives. Conclusions The integration of AI in CSR communication is an evolving field, with significant contributions from social media research and consumer behaviour studies. Future research should address ethical concerns and long-term effects on consumer trust and engagement.
Keywords: M14; O33; 330; CSR communication; AI; Consumer; CiteSpace; bibliometric